Saudi Arabia's Digital and Distance Education : Experiences from the COVID-19 Pandemic and Opportunities for Educational Improvement - Boni, Anna (Washington, DC: World Bank, 2022)
Faced with the crisis of the Coronavirus disease 2019 (COVID-19) pandemic in March 2020, Saudi Arabia embarked on a journey to adapt the way in which schooling operated, enabling a continued education for children across the country. This was a unique journey, and one that will have lasting impacts on education in Saudi Arabia. The World Bank studied this journey in detail over the 2020-21 school year, as the pandemic was underway. This report compiles the results of this study and provides a comprehensive review of the experiences of digital and distance education in Saudi Arabia, along with an analysis of opportunities for future educational improvement. The study aimed to answer three main questions. Firstly, how well did Saudi Arabia provide for, and achieve, continued education of kindergarten to grade 12 (K-12) students during the COVID-19 pandemic Secondly, what were the strengths of Saudi Arabia’s response to the COVID-19 pandemic in K-12 education And finally, what are the opportunities for educational improvement following the digital and distance education experience To answer these questions, a variety of data gathering instruments were designed and implemented by the World Bank team. The data sources included focus groups; surveys of nationally representative groups of school principals, teachers, students, parents, and supervisors; virtual classroom observations; and interviews with key personnel. Analyses of these data informed the conclusions and recommendations presented in this report, which were reviewed by global experts in the fields of education and education technologies.